The Effectiveness of SKKNI Based Motorcycle Technician Training to Increase the Competitiveness of the Regional Automotive Workforce - Abdillah, Fuad (Indonesian Journal Publisher, 2025)
The purpose of this study is to evaluate the effectiveness of motorcycle technician training based on the Indonesian National Work Competency Standards (SKKNI) in enhancing the competitiveness of the workforce in the automotive industry in specific areas. Although injection motorcycle technology has become the industry standard, a labor competency gap still hinders business. This study employs a quantitative approach with a descriptive-analytical design to collect data from 32 alums of UPT-BLK training in Grobogan Regency, using non-participatory observation, documentation, questionnaires, and literature reviews. The data were analyzed using multiple linear regression in SPSS. The results showed that the variables of Labor Needs (X1) and SKKNI Standard Injection Motorcycle Service (X2) contributed 95.5% to the Industrial World variable (Y). The value of the calculated F (21.399) is greater than the F of the table (2.69), and the significance of 0.045 is lower than 0.05. According to the t-test, Labor Needs had a positive and significant effect (t = 3.276; p = 0.082). On the other hand, SKKNI-standard service schemes show adverse effects, which require further investigation. This study demonstrates that SKKNI-based training is generally effective in enhancing the skills of technicians and addressing the gaps between vocational training and industrial needs. These results make a strategic contribution to the development of competency-based training policies and suggest that the curriculum be adapted to the needs of the job market in the current era of vehicles.